2006
DOI: 10.1002/neu.20219
|View full text |Cite
|
Sign up to set email alerts
|

Auditory topography and temporal response dynamics of canary caudal telencephalon

Abstract: To map the encoding of auditory cues in songbirds, multiunit electrophysiological responses to pure tone stimuli (250-5000 Hz) were recorded at 373 sites throughout the avian analogue of the mammalian auditory cortex in the caudal telencephalon of awake, restrained canaries. We found that a dorso-ventral tonotopic gradient from low to high frequency stimuli extends from the rostral field L2 to caudal-most caudo-medial nidopallium (NCM), similar to the frequency-dependent patterns of ZENK gene expression in can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 24 publications
8
48
0
Order By: Relevance
“…These include the primary termination site of the ascending auditory pathway in the nidopallium (termed field L) and adjacent higher-order areas, including the caudomedial nidopallium (NCM), the caudomedial mesopallium (CMM), the shelf region adjacent to the HVC, and the cup region adjacent to the RA [30][31][32]. These regions show strong activation when songbirds hear conspecific songs, based on the robust induction of activity-dependent immediate early genes (IEGs) [33][34][35][36] and/or electrophysiological responses [37][38][39][40][41][42]. Since these or similar areas seem to be present in all birds studied to date [43], regardless of the occurrence of vocal learning, they are likely to play general roles in auditory processing.…”
Section: Doi 101002/bies201000150mentioning
confidence: 98%
“…These include the primary termination site of the ascending auditory pathway in the nidopallium (termed field L) and adjacent higher-order areas, including the caudomedial nidopallium (NCM), the caudomedial mesopallium (CMM), the shelf region adjacent to the HVC, and the cup region adjacent to the RA [30][31][32]. These regions show strong activation when songbirds hear conspecific songs, based on the robust induction of activity-dependent immediate early genes (IEGs) [33][34][35][36] and/or electrophysiological responses [37][38][39][40][41][42]. Since these or similar areas seem to be present in all birds studied to date [43], regardless of the occurrence of vocal learning, they are likely to play general roles in auditory processing.…”
Section: Doi 101002/bies201000150mentioning
confidence: 98%
“…These areas are likely to be modulated by experience and learning. Indeed, unit recordings show that neuronal responses are more selectively tuned to learned vocal sounds in NCM (20,21) and CM (43)(44)(45), whereas the primary auditory subregions L2a and L2b are responsive to sounds within the wider species-specific spectrotemporal range (24,46,47). Measurement of long-term response habituation in NCM, by both electrophysiology and the study of the song stimulation-induced up-regulation of ZENK, has suggested that this area might encode the long-lasting sensory memory of the TUT (31,40).…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 99%
“…In parallel with song motor learning, auditory song selectivity gradually emerges during development (13)(14)(15)(16)(17). Robust sensory responses to auditory stimuli have been recorded in the primary auditory area in the caudal telencephalic region (field L), the caudomedial nidopallium (NCM), the caudal mesopallium (CM), and the caudomedial ventral hyperstriatum (18)(19)(20)(21), as well as in the song nuclei HVC, LMAN, X, and nucleus interface of the nidopallium (22)(23)(24)(25)(26)(27)(28). Sensory representation of birdsong in the song nuclei and the secondary auditory areas NCM and CM is characterized by response selectivity to song ownership, familiarity, and species-specific features.…”
mentioning
confidence: 99%
“…ZENK has been widely employed to identify cell populations in the brain that are involved in both production and perception of communication signals [Mello et al, 1992;Jarvis and Nottebohm, 1997;Duffy et al, 1999;Stripling et al, 2001;Bailey et al, 2002;Hoke et al, 2006;Terleph et al, 2006;Lynch and Wilczynski, 2008]. In birds, ZENK induction in the auditory forebrain is typically higher in individuals exposed to conspecific songs as compared to heterospecific songs [Mello et al, 1992].…”
Section: Introductionmentioning
confidence: 99%